Understanding utilitarianism - Mulgan, Tim (Understanding movements in modern thought., 2014)
Utilitarianism - a philosophy based on the principle of the greatest happiness for the greatest number of people - has been hugely influential over the past two centuries. Beyond ethics or morality, utilitarian assumptions and arguments abound in modern economic and political life, especially in public policy. An understanding of utilitarianism is indeed essential to any understanding of contemporary society. ""Understanding Utilitarianism"" presents utilitarianism very much as a living tradition. The book begins with a summary of the classical utilitarianism of the eighteenth and nineteenth c